Pengaruh Strategi Perubahan Nilai Car Terhadap Jangkauan Layanan Dan Risiko Pembiayaan Pada Lkm Koperasi Sejahtera Bangsaku - Ade Rachmawan; Abdul Kohar; tb. Nur Ahmad Maulana (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2016)
The role of micro credit in poverty alleviation is very important. In Indonesia, performed by the Commercial Bank/ Islamic Banks of micro units, cooperative, rural bank/rural Islamic bank, and MFIs. Outreach microfinance services to the poor andmicro enterprisesin Indonesia is still very low. Perception of high risk for micro credit, especially loans to the poor/micro enterprises and lack of capital adequacy ratio (CAR) of rural bank/rural Islamic bank/ cooperative become obstacles for Financial institutions microlenders intermediation to the poor/micro enterprises or to financial institutions that will collaborate with MFIs in micro lending. Standardized Model approach is the basis for calculating CAR for Financial institutions microlendersin Indonesia. This method gives a risk weighting of 100% in the assessment of credit risk as a component of Risk Weighted Assets (RWA). CreditRisk+ method is a method of measuring credit risk models based on credit default approach that describes the amount and time limit information exposure and measurement of systematic credit risk of the borrower. By using this method, the credit risk is calculated as the ratio of the maximum estimate of bad debts to the credit balance. For MFIs with good performance of the NPL, then the value of RWA will be smaller, therefore the CAR is much bigger than the results of model calculations the standardized approach. With this result, outreach MFI services will increase as investors would not hesitate to cooperate in the delivery of microfinance to poor communities/micro enterprises.